2015
DOI: 10.28945/2135
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Computer Simulation to Compare Student performance in Traditional versus Distance Learning Environments

Abstract: Simulations have been shown to be an effective tool in traditional learning environments; however, as distance learning grows in popularity, the need to examine simulation effectiveness in this environment has become paramount. A casual-comparative design was chosen for this study to determine whether students using a computer-based instructional simulation in hybrid and fully online environments learned better than traditional classroom learners. The study spans a period of 6 years beginning fall 2008 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
2
1
0
Order By: Relevance
“…The result is also consistent with the findings of Ezeudu and Ezinwanne (2013) that the achievement of students in chemistry increased after being taught with computer simulation. Furthermore, the result of the study is consistent with the results of Boutefnouchet and Laios (2016) and Guy and Lownes-Jackson (2015). On the contrary, this result negates the result obtained by Bayrak (2007) who found that there was no significant difference in the effectiveness of using computer simulated and laboratory instructions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The result is also consistent with the findings of Ezeudu and Ezinwanne (2013) that the achievement of students in chemistry increased after being taught with computer simulation. Furthermore, the result of the study is consistent with the results of Boutefnouchet and Laios (2016) and Guy and Lownes-Jackson (2015). On the contrary, this result negates the result obtained by Bayrak (2007) who found that there was no significant difference in the effectiveness of using computer simulated and laboratory instructions.…”
Section: Resultssupporting
confidence: 88%
“…Guy and Lownes-Jackson (2015) carried out an experimental study to compare the effect of computer simulation and the traditional instructional method on students' achievement in microcomputer application course. The study which was conducted in College of Business at Tennessee State University found that students who were taught with computer simulation performed better than students taught with traditional method.…”
Section: Computer Simulation/simulated Instructional Approachmentioning
confidence: 99%
“…This result implies that the simulation-based instruction used in the current study is repeatable because of the tool used in the three different classes with three different science teachers. The result is also in line with other studies (Guy & Lownes-Jackson, 2015;Odadžić et al, 2017). It is obvious that simulation-based instructions are precious tools for enhancing students' conceptual knowledge in science topics (Faour, & Ayoubi, 2018;Renken & Nunez, 2013) because the environment provides simplification for eliminating distractors, so students can easily focus on the subject (ChanLin, 2001;Hebebci et al, 2014;Trundle & Bell, 2010).…”
Section: Discussionsupporting
confidence: 93%